Nanoparticle-Loaded Polarized-Macrophages for Enhanced Tumor Targeting and Cell-Chemotherapy - Hou, Teng; Wang, Tianqi; Mu, Weiwei; Yang, Rui; Liang, Shuang; Zhang, Zipeng; Fu, Shunli; Gao, Tong; Liu, Yongjun; Zhang, Na (Nano-Micro Letters, 2020)
Cell therapy is a promising strategy for cancer therapy. However, its therapeutic efficiency remains limited due to the complex and immunosuppressive nature of tumor microenvironments. In this study, the “cell-chemotherapy” strategy was presented to enhance antitumor efficacy. M1-type macrophages, which are therapeutic immune cells with both of immunotherapeutic ability and targeting ability, carried sorafenib (SF)-loaded lipid nanoparticles (M1/SLNPs) were developed. M1-type macrophages were used both as therapeutic tool to provide immunotherapy and as delivery vessel to target deliver SF to tumor tissues for chemotherapy simultaneously. M1-type macrophages were obtained by polarizing macrophages using lipopolysaccharide, and M1/SLNPs were obtained by incubating M1-type macrophages with SLNP. Tumor accumulation of M1/SLNP was increased compared with SLNP (p < 0.01), which proved M1/SLNP could enhance tumor targeting of SF. An increased ratio of M1-type macrophages to M2-type macrophages, and the CD3+CD4+ T cells and CD3+CD8+ T cell quantities in tumor tissues after treatment with M1/SLNP indicated M1/SLNP could relieve the immunosuppressive tumor microenvironments. The tumor volumes in the M1/SLNP group were significantly smaller than those in the SLNP group (p < 0.01), indicating M1/SLNP exhibited enhanced antitumor efficacy. Consequently, M1/SLNP showed great potential as a novel cell-chemotherapeutic strategy combining both cell therapy and targeting chemotherapy. Highlights: 1 A polarized-macrophages-based drug delivery system (M1/SLNP) was presented for the cell-chemotherapy of cancer. 2 Polarized-macrophages were used both as therapeutic tool to provide immunotherapy and as delivery vessel to target deliver chemotherapeutic drugs to tumor tissues for chemotherapy simultaneously. 3 M1/SLNP was a multifunctional delivery system with simple structure, excellent safety, and without complex synthesis process.